Palynological study of the carboniferous sequence at Río Francia Creek,Paganzo Basin, Argentina - Perez Loinaze, Valeria Susana (2011)
Well-preserved palynological assemblages have been obtained from the Guandacol Formation at Rio Francia Creek, Paganzo Basin, Argentina. The geological setting and stratigraphic provenance of the samples is provided. Forty-nine spore, twenty-three pollen and two algal species are identified. Some species are recognized for the first time from this unit, such as: Brevitriletes levis, B. leptoacaina, Lundhladispora areolata, Peppersites ellpticus, Psomospora detecta, Rattiganispora apiculata and Retusotriletes nigritelus. These assemblages are referred to Subzone A of the Raistrickia densa-Convolutispora muriornata Biozone, late Serpukhovian-early Bashkirian in age. Palynological samples from the Tupe Formation at the same locality were studied in order to compare the composition of both units, which present a palynological composition similar to the associations recovered from the Guandacol Formation. Spelaeotriletes ybertii is restricted to the palynological assemblages of the Tupe Formation studied herein. It is noteworthy that both units lack taeniate pollen. Some species restricted at this locality to the Guandacol Formation, have a wider stratigraphic distribution elsewhere. The only species from this unit that seems to have biostratigraphic significance is Tricidaricporites gutii. A new species of trilete spores is proposed, i.e., Cyclogranisporites cuerdae sp. nov. from the Tupe Formation.